2009
DOI: 10.1016/j.bpj.2009.08.047
|View full text |Cite
|
Sign up to set email alerts
|

High-Chloride Concentrations Abolish the Binding of Adenine Nucleotides in the Mitochondrial ADP/ATP Carrier Family

Abstract: The ADP/ATP carrier (AAC) is a very effective membrane protein that mediates the exchange of ADP and ATP across the mitochondrial membrane. In vivo transport measurements on the AAC overexpressed in Escherichia coli demonstrate that this process can be severely inhibited by high-chloride concentrations. Molecular-dynamics simulations reveal a strong modification of the topology of the local electric field related to the number of chloride ions inside the cavity. Halide ions are shown to shield the positive cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…A report [44] indicates that sensory rhodopsin has a binding site for Cl -, which regulates rhodopsin activity. Further, it has been reported that Cl -regulates mitochondrial ADP/ATP carrier by inhibiting the binding of adenine nucleotides to the carrier [45], and that ENaC activity in the kidney is regulated intracellular Cl - [33]. These reports and our observations in the present study suggest that Cl -plays important roles in cell functions.…”
Section: Discussionsupporting
confidence: 80%
“…A report [44] indicates that sensory rhodopsin has a binding site for Cl -, which regulates rhodopsin activity. Further, it has been reported that Cl -regulates mitochondrial ADP/ATP carrier by inhibiting the binding of adenine nucleotides to the carrier [45], and that ENaC activity in the kidney is regulated intracellular Cl - [33]. These reports and our observations in the present study suggest that Cl -plays important roles in cell functions.…”
Section: Discussionsupporting
confidence: 80%
“…In its crystallographic structure, AAC is in a conformation open toward the inter-membrane space, fully occluded on the matrix side and impervious to water or any other small substrate 19,21,44 . The MD simulations performed here enlighten, however, striking differences in the structure of the two proteins.…”
Section:  Discussionmentioning
confidence: 99%
“…The positively charged carrier residues, which electrostatically interact with the phosphate groups, drive the passage of the substrate through the cavity to its bottom [21,22]. In fact, high chloride concentration conditions cause inhibition of binding and the further transport of nucleotides [23]. Moreover, tyrosine residues facing the cavity are the targets of SRC kinases that modulate transport by phosphorylation [24].…”
Section: Introductionmentioning
confidence: 99%